2023
DOI: 10.3390/pathogens12111359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Genetic Diversity of the Enteric Protozoan Parasite Blastocystis sp. in the Northern Egypt Population

Doaa Naguib,
Nausicaa Gantois,
Jeremy Desramaut
et al.

Abstract: Blastocystis sp. is currently reported as the most frequent single-celled eukaryote inhabiting the intestinal tract of humans and a wide range of animal groups. Its prevalence is especially higher in developing countries linked with fecal peril. Despite a growing interest in this enteric protozoan, certain geographical regions potentially at high risk of infection, such as North Africa, remain under-investigated. Therefore, a large-scale molecular epidemiological survey, including 825 participants presenting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Additionally, ST10 has been detected in other animals including pigs, deer, bears, antelopes, chickens, swans, and wild birds [ 6 , 7 , 31 ]. Although human infections with ST10 have been relatively rare, reports of this subtype have emerged in Senegalese school children and Egyptians since 2020 [ 8 , 11 ]. Recently, a study conducted in Vietnam revealed that ST10 ranks second highest in humans after ST3 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ST10 has been detected in other animals including pigs, deer, bears, antelopes, chickens, swans, and wild birds [ 6 , 7 , 31 ]. Although human infections with ST10 have been relatively rare, reports of this subtype have emerged in Senegalese school children and Egyptians since 2020 [ 8 , 11 ]. Recently, a study conducted in Vietnam revealed that ST10 ranks second highest in humans after ST3 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its predominant transmission via the fecal-oral route, its prevalence is particularly alarming in developing countries, where poor sanitary and hygiene conditions and unavailability of effective water treatment facilitate the circulation of intestinal parasites [9]. Consequently, its frequency may well exceed 50% in human cohorts, as evidenced in recent epidemiological surveys conducted, for instance, in African countries [10][11][12].…”
Section: Introductionmentioning
confidence: 99%